An annotated catalogue of the Phaegopterina (Erebidae, Arctiinae, Arctiini) of state of Maranhão, Brazil - Silva, Karoline M.o.; Câmara, Joseleide T.; Teston, José A. (Zootaxa, 2023)
Phaegopterina moths comprise approximately 750 species recorded in Brazil. In the Cerrado, there are 254 recorded species, while in the Amazon region there are 469. In this study we present an annotated catalogue of species distribution for the Phaegopterina subtribe, recorded in the state of Maranhão for 11 municipalities. After examining the material and reviewing the bibliography, we developed a catalogue containing 119 species within 59 genera of Phaegopterina, of which 26 species are newly recorded for Maranhão, Brazil. The continuous inventory of Arctiinae for Maranhão will contribute to the identification and understanding of the diversity of Lepidoptera present in the region between the Cerrado and Amazon biomes.